α‐Synuclein species as potential cerebrospinal fluid biomarkers for dementia with lewy bodies - van Steenoven, Inger (Mov Disord, 2018)
Background: The objective of this study was to investigate the discriminating value of a range of CSF α‐synuclein species for dementia with Lewy bodies compared with Alzheimer's disease, PD, and cognitively normal controls. Methods: We applied our recently published enzyme‐linked immunosorbent assays to measure the CSF levels of total α‐synuclein, oligomeric α‐synuclein, and phosphorylated α‐synuclein in dementia with Lewy bodies (n = 42), Alzheimer's disease (n = 39), PD (n = 46), and controls (n = 78). General linear models corrected for age and sex were performed to assess differences in α‐synuclein levels between groups. We used backward‐elimination logistic regression analysis to investigate the combined discriminating value of the different CSF α‐synuclein species and Alzheimer's disease biomarkers. Results: CSF levels of total α‐synuclein were lower in dementia with Lewy bodies and PD compared with Alzheimer's disease as well as controls (P < 0.001). In contrast, CSF levels of oligomeric α‐synuclein were higher in dementia with Lewy bodies and PD compared with Alzheimer's disease (P < 0.05) and controls (P < 0.001). No group differences were found for phosphorylated α‐synuclein. In dementia with Lewy bodies and PD, CSF total α‐synuclein levels positively correlated with tau and phosphorylated tau (both r > 0.40, P < 0.01), but not with amyloid‐β(1‐42). The optimal combination to differentiate dementia with Lewy bodies from controls consisted of amyloid‐β(1‐42), tau, total α‐synuclein, oligomeric α‐synuclein, age, and sex (AUC, 0.90). To differentiate dementia with Lewy bodies from Alzheimer's disease, the combination of tau and oligomeric α‐synuclein resulted in an AUC of 0.83. CSF α‐synuclein species do not contribute to the differentiation of dementia with Lewy bodies from PD. Conclusions: CSF α‐synuclein species could be useful as part of a biomarker panel for dementia with Lewy bodies. Evaluating both oligomeric α‐synuclein and total α‐synuclein in CSF helps in the diagnosis of dementia with Lewy bodies. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.